Learning : principles and applications - Klein, Stephen B. (Los Angeles : SAGE, 2009)
A revised edition of the text for the undergraduate course on learning. The pedagogy remains a central feature of this edition, providing a presentation of the basic principles and description of research studies
Includes bibliographical references
Keywords: Learning; Conditioned response